2005
DOI: 10.1016/j.ejso.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two invasive techniques in the management of intractable pain due to inoperable pancreatic cancer: neurolytic celiac plexus block and videothoracoscopic splanchnicectomy

Abstract: Both NCPB and VSPL provide significant reduction of pain and improvement of quality of life in inoperable pancreatic cancer patients. They present rather similar efficacy, but lower invasiveness of NCPB, in combination with its more positive effect on quality of life, pre-disposes it as being the preferred method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 29 publications
2
50
0
5
Order By: Relevance
“…Stefaniak et al [ 19 ] found that both techniques had similar ef fi cacy in pain reduction and decreased daily opioid consumption. Celiac plexus neurolysis, however, was found to be associated with signi fi cantly improved physical, emotional, and social well-being with the added bene fi t of being less invasive [ 19 ] . As mentioned previously, in the meta-analysis by Eisenberg et al [ 2 ] , positive short-term outcomes from celiac plexus neurolysis, regardless of imaging modality used, were reported ( Fig.…”
Section: Transaortic Approachmentioning
confidence: 97%
See 2 more Smart Citations
“…Stefaniak et al [ 19 ] found that both techniques had similar ef fi cacy in pain reduction and decreased daily opioid consumption. Celiac plexus neurolysis, however, was found to be associated with signi fi cantly improved physical, emotional, and social well-being with the added bene fi t of being less invasive [ 19 ] . As mentioned previously, in the meta-analysis by Eisenberg et al [ 2 ] , positive short-term outcomes from celiac plexus neurolysis, regardless of imaging modality used, were reported ( Fig.…”
Section: Transaortic Approachmentioning
confidence: 97%
“…One study found no difference in pain scores with neurolysis between the retrocrural, transaortic, and bilateral chemical splanchnicectomy groups [ 10 ] . In a nonrandomized, prospective, case-controlled study of 59 patients [ 19 ] , celiac plexus neurolysis was compared to videothorascopic splanchnicectomy. Stefaniak et al [ 19 ] found that both techniques had similar ef fi cacy in pain reduction and decreased daily opioid consumption.…”
Section: Transaortic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would like to emphasize the fact that this study was an initial report of a larger prospective, randomized study comparing the quality of life, subjective pain perception, survival and costs of BVSPL, neurolytic celiac plexus block (NCPB) and conservative treatment (15,16). We would like to invite each and every surgical department in Poland to participate in the study offering hands-on training in the surgical technique and internet tools necessary for reliable evaluation of operated cases.…”
Section: Discussionmentioning
confidence: 99%
“…As the celiac plexus contains a large portion of the afferent nerve fibers from the pancreas, several studies have tested the efficieny of celiac plexus blockade/neurolysis in the treatment of pain due to PCa. In all these studies, patients had significant pain relief (Wong et al, 2004;Stefaniak et al, 2005;Yan&Myers, 2007) following this intervention. While the efficiency of this "denervation" technique does not necessarily prove the neuropathic character of pain in PCa, it underlines the deciding contribution of nerves and the transmitted signals in the generation of the pain syndrome in PCa Considering the neuropathic character of pain in PCa, one can assume that neuropathic analgesics may be of benefit to treat PCa-associated pain.…”
Section: The Role Of Neural Invasion In the Pain Due To Pcamentioning
confidence: 99%